1995
DOI: 10.1002/art.1780380818
|View full text |Cite
|
Sign up to set email alerts
|

Development of an observation method for assessing pain behaviors in children with juvenile rheumatoid arthritis

Abstract: Objective. To develop an observation method for assessing pain behaviors in children with juvenile rheumatoid arthritis (JRA).Methods. Thirty children with JRA performed a standardized sequence of activities for video recording, and correlations between the pain behaviors observed on the videotapes and established measures of pain, depression, and functional disability were determined.Results. Pain behaviors were reliably observed (kappa coefficients 0.53-0.79). Total pain behaviors were significantly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…All patients were evaluated using an objective observation method to record motor pain behaviors. We recently validated this observation method in adult patients with fibromyalgia (38), and others have documented the reliability and validity of this method in children and adolescents with juvenile rheumatoid arthritis (39). The observation protocol consisted of a 10-minute videotaped session in which the patient engaged in a standard, timed set of activities: sitting, walking, standing, and reclining.…”
Section: Measures Coping Strategies Questionnaire Formentioning
confidence: 99%
“…All patients were evaluated using an objective observation method to record motor pain behaviors. We recently validated this observation method in adult patients with fibromyalgia (38), and others have documented the reliability and validity of this method in children and adolescents with juvenile rheumatoid arthritis (39). The observation protocol consisted of a 10-minute videotaped session in which the patient engaged in a standard, timed set of activities: sitting, walking, standing, and reclining.…”
Section: Measures Coping Strategies Questionnaire Formentioning
confidence: 99%
“…The difference is due to the fact that children older than 2 years have good neurological motor maturity and that, in our context, children had no limitation of mobility, except pain. Hence, more explicit qualitative behavioural changes can be observed in these children, such as guarded movement (Jaworski et al, 1991) and abnormal patterns of movement, as observed by Truckenbrodt (1993) in children with juvenile rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 72%
“…Jaworski et al [21] proposed that children who experience pain secondary to JRA also would demonstrate specific, identifiable, and quantifiable pain behaviors, similar to those that have been observed in adults with RA. Their study investigated the usefulness of a behavioral observation method, similar to that developed for adult RA patients by McDaniel et al [ZO], for assessing pain behaviors in pediatric patients with chronic JRA.…”
Section: Behavioral Observations Of Pain Behaviorsmentioning
confidence: 95%